Sustainable Urban Space Development based on The Needs of Urban Communities : Case Study Bandung Raid Party - Widagdo, Rama Arianto; Fakhriza, Muhammad (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2025)
Sustainable urban spaces are the right of every urban dweller. As an eminent user of urban spaces, the preferences of citizens need to be considered in developing an urban environment. Urban dweller preferences include various aspects, which include their favourite activities and hobbies. Citizen’s favourite activities and hobbies are commonly accommodated by establishing urban communities. Consequently, these communities should be able to provide recommendations for ensuring effective and efficient sustainable development. This study aims to formalize the connection between reasonable development based on urban community activities. Bandung Raid Party was the urban community elected for this study in consideration of their direct interaction with urban spaces, their members coming from various backgrounds, and their ripe age in comparison with other similar communities. Key data and information are gathered through literature study and structured interviews with strategic actors from the community, which are later analyzed using content analysis. After comprehensive analysis and consideration, the research shows how the Bandung Raid Party community observes and appreciates the quality of urban spaces where they hold their activities. The study also shows that their activities can be supported by developing and improving sustainable pedestrian access, public spaces, and urban iconic landmarks. These findings can be initial evidence of how urban communities can provide significant input for sustainable urban development.